Benefit of the doubt: a new view of the role of the prefrontal cortex in executive functioning and decision making - Asp, Erik W.; Manzel, Kenneth; Koestner, Bryan; Denburg, Natalie; Tranel, Daniel (Frontiers in Neuroscience, 2013)
The False Tagging Theory (FTT) is a neuroanatomical model of belief and doubt processes that proposes a single, unique function for the prefrontal cortex. Here, we review evidence pertaining to the FTT, the implications of the FTT regarding fractionation of the prefrontal cortex, and the potential benefits of the FTT for new neuroanatomical conceptualizations of executive functions. The FTT provides a parsimonious account that may help overcome theoretical problems with prefrontal cortex mediated executive control such as the homunculus critique. Control in the FTT is examined via the “heuristics and biases” psychological framework for human judgment. The evidence indicates that prefrontal cortex mediated doubting is at the core of executive functioning and may explain some biases of intuitive judgments